Molecular characterization and interactome analysis of Trypanosoma cruzi tryparedoxin II - Arias, Diego Gustavo (2015)
Trypanosoma cruzi, the causative agent of Chagas disease, possesses two tryparedoxins (. TcTXNI and TcTXNII), belonging to the thioredoxin superfamily. TXNs are oxidoreductases which mediate electron transfer between trypanothione and peroxiredoxins. This constitutes a difference with the host cells, in which these activities are mediated by thioredoxins. These differences make TXNs an attractive target for drug development. In a previous work we characterized TcTXNI, including the redox interactome. In this work we extend the study to TcTXNII. We demonstrate that TcTXNII is a transmembrane protein anchored to the surface of the mitochondria and endoplasmic reticulum, with a cytoplasmatic orientation of the redox domain. It would be expressed during the metacyclogenesis process. In order to continue with the characterization of the redox interactome of T. cruzi, we designed an active site mutant TcTXNII lacking the resolving cysteine, and through the expression of this mutant protein and incubation with T. cruzi proteins, heterodisulfide complexes were isolated by affinity chromatography and identified by mass spectrometry. This allowed us to identify sixteen TcTXNII interacting proteins, which are involved in a wide range of cellular processes, indicating the relevance of TcTXNII, and contributing to our understanding of the redox interactome of T. cruzi. Biological significance: T. cruzi, the causative agent of Chagas disease, constitutes a major sanitary problem in Latin America. The number of estimated infected persons is ca. 8 million, 28 million people are at risk of infection and ~. 20,000 deaths occur per year in endemic regions. No vaccines are available at present, and most drugs currently in use were developed decades ago and show variable efficacy with undesirable side effects. The parasite is able to live and prolipherate inside macrophage phagosomes, where it is exposed to cytotoxic reactive oxygen and nitrogen species, derived from macrophage activation. Therefore, T. cruzi antioxidant mechanisms constitute an active field of investigation, since they could provide the basis for a rational drug development.Peroxide detoxification in this parasite is achieved by ascorbate peroxidase and different thiol-dependent peroxidases. Among them, both mitochondrial and cytosolic tryparedoxin peroxidases, typical two-cysteine peroxiredoxins, were found to be important for hydrogen peroxide and peroxynitrite detoxification and their expression levels correlated with parasite infectivity and virulence. In trypanosomes tryparedoxins and not thioredoxins act as peroxiredoxin reductases, suggesting that these enzymes substitute thioredoxins in these parasites. T. cruzi possesses two tryparedoxin genes, TcTXNI and TcTXN II.Since thioredoxins are proteins with several targets actively participating of complex redox networks, we have previously investigated if this is the case also for TcTXNI, for which we described relevant partners (J Proteomics. 2011;74(9):1683-92). In this manuscript we investigated the interactions of TcTXNII. We have designed an active site mutant tryparedoxin II lacking the resolving cysteine and, through the expression of this mutant protein and its incubation with T. cruzi proteins, hetero disulfide complexes were isolated by affinity chromatography purification and identified by electrophoresis separation and MS identification. This allowed us to identify sixteen TcTXNII interacting proteins which are involved in different and relevant cellular processes. Moreover, we demonstrate that TcTXNII is a transmembrane protein anchored to the surface of the mitochondria and endoplasmic reticulum.